Wittgenstein and philosophy of religion - Arrington, Robert L., 1938-2015; Addis, Mark (Routledge, 2001)
Wittgenstein and Philosophy of Religion is an exciting introduction to the influential and controversial contribution which the later Wittgenstein made to the philosophy of religion.
Keywords: Wittgenstein, Ludwig, -- 1889-1951 -- Contributions in philosophy of religion.; Wittgenstein, Ludwig, -- 1889-1951; Religion -- Philosophy.; Religion -- Philosophie.; RELIGION -- Philosophy.; Religion -- Philosophy; Godsdienstfilosofie.; Humaniora -- Filosofi.